2017
DOI: 10.1021/acs.jpcc.6b13016
|View full text |Cite
|
Sign up to set email alerts
|

XPS Analysis of the Improved Operational Stability of Organic Solar Cells Using a V2O5 and PEDOT:PSS Composite Layer: Effect of Varied Atmospheric Conditions

Abstract: This work investigates the enhanced stability of organic solar cells (OSCs) fabricated with a hybrid hole-transport layer (HTL) incorporating vanadium pentaoxide (V2O5) nanoparticles in poly­(3,4-ethylenedioxythiophene):poly­(styrenesulfonate) (PEDOT:PSS). OSCs have been fabricated in controlled and ambient atmospheric conditions by employing a pristine PEDOT:PSS HTL and its hybrid variant. Stability and degradation analyses were carried out by using photovoltaic and X-ray photoelectron spectroscopy (XPS) meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 43 publications
(90 reference statements)
1
27
0
Order By: Relevance
“…incorporated vanadium oxide (V 2 O 5 ) into the PEDOT:PSS based hole transport layer and found that the air stability of the device can be profoundly improved. [ 147 ]…”
Section: Progress In Enhancing Stabilitymentioning
confidence: 99%
“…incorporated vanadium oxide (V 2 O 5 ) into the PEDOT:PSS based hole transport layer and found that the air stability of the device can be profoundly improved. [ 147 ]…”
Section: Progress In Enhancing Stabilitymentioning
confidence: 99%
“…Another advantageous specificity lies in the facility to improve the electrochromic properties by single or double doping or by addition of other materials and formation of composites [19][20][21][22]. Doping of material in electrochromic host lattice is expected to benefit the coloration efficiency and durability of the host, extending the switching potential range, and enhancing the reaction kinetics [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The XPS analysis of PEDOT/CP (Figure ) further proves the surface function of the CP and composition of the PEDOT/CP electrode. Apart from the peaks corresponding to the sp2‐hybridized CC (284.8 eV) and the sp3‐hybridized CC (285.1 eV) bonds in the structure of PEDOT, the peaks at 532.9 and 163 eV reveal the existence of S and O element, indicating the successful electrodeposition of the PEDOT on the CP surface …”
Section: Resultsmentioning
confidence: 99%
“…Apart from the peaks corresponding to the sp2-hybridized C C (284.8 eV) and the sp3-hybridized C C (285.1 eV) bonds in the structure of PEDOT, the peaks at 532.9 and 163 eV reveal the existence of S and O element, indicating the successful electrodeposition of the PEDOT on the CP surface. 39,40 The Thermal Properties of PVA/H 2 SO 4 /KI Electrolyte Figure 4 shows the DSC and TGA curves of PVA/H 2 SO 4 /KI GPE. The peaks observed at 120-150 C are considered as the chain movements caused by water, KI, and other small molecules.…”
Section: Xps Of Pedot/cp Electrodementioning
confidence: 99%